Patient-oriented Evidence-based Treatment Decision Support System (TreatQuest®) for Lung Cancer - (:unkn) unknown (My University, 2013)
Involving patients in healthcare decisions makes a significant and enduring difference to healthcare outcomes. One challenge for patients is the lack of evidence-based information and tools to support their decision making. Although patients have access to significant information through internet and other sources, it is not personalized for their specific situation. This dissertation attempts to help patients acquire evidence-based information relevant to their own situation, so they can make a more informed decision in co-operation with their physicians. Lung cancer has been selected as a focus for this study because lung cancer presents very complex decision making situation and is the leading cause of cancer deaths in both men and woman in every ethnic group worldwide. The prototype decision support system for lung cancer is called TreatQuest®. This system allows users to create their own profile, access cases similar to their case, and learn about treatment options. The evidences for the treatment were extracted from public data and knowledge gained from guideline. The effectiveness of patient-oriented evidence-based approach was validated by having a group of patient use the system. TreatQuest® is one of the first system developed to support patient's treatment decision process, which represent the most recent trend in delivery of healthcare services. Results from this study show that such a patient-oriented decision support system provides an effective way to help patient receive more personalized information and make informed treatments. In summary, patient-oriented evidence-based decision support systems such as TreatQuest®, can improve the decision quality for patients. Also, such systems can improve health care decisions that are made with the active participation of fully informed patients. Therefore, patient-oriented evidence-based decision support systems can have significant impact on the healthcare industry.
Keywords: Decision Support System; Evidence-based; Guideline; Lung Cancer; Patient-Oriented